Ways of Forming Personal and Social-Labour Functions of a Future Teacher - Tangkish, Nazira P.; Kamalov, Yussubaly N.; Aripzhan, Gulnur; Kairakbaeva, Hanzada; Duisebaeva, Gulnara; Erbota, Ainur S. (Journal of Intellectual Disability - Diagnosis and Treatment, 2020)
Objective: The relevance of research is determined by the fact that it allows identifying the main criteria by which the development of a teacher is ensured both at the level of personal development and at the level of improving labour functions. The authors understand the complex development of personal and social-labour functions of a teacher as self-development in the process of fulfilling professional relations. Background: Each of the participants in the educational process must meet the requirements set by state educational standards. With that, the personal qualities of a teacher should be fully correlated with the necessity of improving labour parameters. Method: The effectiveness of the introduction of pedagogical conditions, which had a significant impact on the professional self-development of teachers, was tested experimentally with the use of anthropocentric and activity-based approaches to studying the problem, as well as with the use of the statistical method. Results: The analysis presented in the paper showed that the indicated pedagogical conditions contribute to the formation of professional motivation, focus on the professional self-development of teachers, a high level of aspirations, awareness of the value of individual professional self-development, the ability to notice shortcomings, develop social skills and communication skills of teachers. Conclusion: It was determined that the socio-psychological climate in an institution, where there is organisational support from the administration and informational support from other specialists, contributes to the development of operational-activity and reflective and value-based components.